Sox9 in the epicardium: Implications for cell invasion, differentiation, and coronary vascular development - Andrew B. Harvey; Allison M. Trouten; Renélyn A. Wolters; Jenna R. Drummond; Raymond N. Deepe; Hannah G. Tarolli; Inara Devji; Silvia G. Vaena; Martin J. Romeo; Robin Muise-Helmericks; Paula S. Ramos; Russell A. Norris; et al. (PLoS ONE, 2025)
The epicardium is the mesothelial lining of the heart and is a source of progenitor cells during heart development, giving rise to an invasive population of mesenchymal cells which differentiate into cardiac fibroblasts, mural cells, and other cell types essential for heart structure and function. Previously, we showed that epicardial-specific deletion of the gene encoding SRY-box transcription factor 9 (SOX9) impairs epicardial-derived cell invasion and reduces their contribution to the atrioventricular valve mesenchyme. In this study, we use single-cell RNA-sequencing to investigate broader roles of Sox9 in the epicardium as it relates to epicardial invasion, differentiation, and vascular development. We identified transcriptional changes indicative of decreased epicardial-to-mesenchymal transformation consistent with histological observations. Immunofluorescence analyses revealed defective epicardial attachment and decreased epicardial-derived cell invasion into the ventricular myocardium associated with delayed coronary plexus formation. Sox9-deficient epicardial cells exhibited elevated expression of vascular smooth muscle cell genes, suggesting that Sox9 may influence epicardial cell fate decisions. This study expands our understanding of the role of Sox9 in epicardial biology, demonstrating an important function in regulating epicardial cell invasion, differentiation, and coronary vasculature development. These insights provide a foundation for further investigations into epicardial-mediated mechanisms underlying congenital heart abnormalities.